Potential of mineral-solubilizing bacteria for physiology and growth promotion of Chenopodium quinoa Willd - Rafique, Ejaz; Mumtaz, Muhammad Zahid; Ullah, Inam; Rehman, Aneela; Qureshi, Kamal Ahmad; Kamran, Muhammad; Rehman, Mujaddad Ur; Jaremko, Mariusz; Alenezi, Muneefah Abdullah (Frontiers in Plant Science, 2022)
Nutrient deficiency in wild plant species, including quinoa (Chenopodium quinoa Willd), can be overcome by applying mineral-solubilizing bacteria. Quinoa is a gluten-free, nutritious food crop with unique protein content. The present study aimed to characterize mineral-solubilizing rhizobacterial strains and to evaluate their plant growth-promoting potential in quinoa seedlings. More than sixty rhizobacterial strains were isolated from the quinoa rhizosphere and found eighteen strains to be strong phosphate solubilizers. Most of these bacterial strains showed zinc solubilization, and more than 80% of strains could solubilize manganese. The selected strains were identified as Bacillus altitudinis Cq-3, Pseudomonas flexibilis Cq-32, Bacillus pumilus Cq-35, Pseudomonas furukawaii Cq-40, Pontibacter lucknowensis Cq-48, and Ensifer sp. Cq-51 through 16S rRNA partial gene sequencing. Mainly, these strains showed the production of organic acids, including malic, gluconic, tartaric, ascorbic, lactic, and oxalic acids in insoluble phosphorus amended broth. All strains showed production of gluconic acids, while half of the strains could produce malic, ascorbic, lactic, and oxalic acids. These strains demonstrated the production of indole-3-acetic acid in the presence as well as in the absence of L-tryptophan. The bacterial strains also demonstrated their ability to promote growth and yield attributes, including shoot length, root length, leave numbers, root and shoot dry biomass, spike length, and spikes numbers of quinoa in pots and field trials. Increased physiological attributes, including relative humidity, quantum flux, diffusive resistance, and transpiration rate, were observed due to inoculation with mineral solubilizing bacterial strains under field conditions. P. lucknowensis Cq-48, followed by P. flexibilis Cq-32, and P. furukawaii Cq-40 showed promising results to promote growth, yield, and physiological attributes. The multi-traits characteristics and plant growth-promoting ability in the tested bacterial strains could provide an opportunity for formulating biofertilizers that could promote wild quinoa growth and physiology.